2nd International Conference on Advances in Plant Sciences (ICAPS 2014) - Chan, Margaret (UiTM Sarawak, 2015)
Universiti Teknologi MARA and the University of Bangalore, India through the Dr Sivaram Research Foundation and the Century Foundation with the support of the Sarawak Convention Bureau organised ICAPS 2014, the second international conference from 18th to 22nd November 2014 at Four Points by Sheraton, Kuching. Delegates from 24 countries convened at this conference to discuss and share advanced information and experiences in advanced plant sciences research across the globe. The organising chairperson, Associate Professor Dr. Margaret Chan, welcomed the delegates and Professor Dr. Sivaram, the President of the conference, officiated at the opening ceremony.